Islam’s Bai’al-khosaroh Practices and Modern Business Practices: An Examination - Pratama, Muhamad Zundi; Nur, Efa Rodiah; Nik Abdullah, Nik Herda Binti (ASAS, 2023)
Competition between traders triggers them to cut prices, this phenomenon causes tight capital traders to be threatened with bankruptcy, dynamics in a market are very diverse, traders have different ways to earn profits either by lawful way or by justifying all kinds of ways, one of which is to play the price market by selling goods below the market price or Bai' Al-Khossaroh. Merchandise that is beyond its production period (expired) and factors of unfair business competition are the reason traders sell their wares using the Bai' Al-Khossaroh practice which causes unstable market prices and many business actors go out of business, Bai' Al-Khossaroh in practice it can be in the form of discounts (discounts), promotions for certain items, as well as including certain gifts on each item sold. An in depth literature review was engaged to discuss Bai' Al-Khossaroh' s practices from the perspective of Islamic law and modern law. Conclusion drawn from the review is that. Bai' Al-Khossaroh does not violate the rules of Islamic law if in practice it brings benefits and does not bring harm to sellers and buyers. Bai' Al-Khossaroh is not permitted if it is not in accordance with the pillars and conditions of sale and purchase and is not in accordance with the principles of Mu'amalah and brings harm to sellers and buyers. Bai' Al-Khossaroh is permitted in law as long as in practice there is no element of monopoly and unfair business competition as stated in Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition. Keyword: Bai', Bai' AL -Khossaroh, Islamic Law, Modern Laws, Monopoly